2015
DOI: 10.1093/hsw/hlv025
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Care Discrimination Experiences among a National Sample of Female-to-Male Transgender Individuals

Abstract: Transgender individuals experience harassment, violence, and discrimination in a number of settings. Although health care discrimination against transgender people has been documented, this issue is understudied. Using a national cross-sectional survey data set (N = 1,711), the authors sought to determine how gender identity and presentation predict health care discrimination experiences among female-to-male (FTM) transgender people after demographic and socioeconomic characteristics are controlled. Analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 18 publications
3
86
1
Order By: Relevance
“…Negative health care experiences were, in addition, found to be associated with poor self-rated health, self-reported disability and lower quality of life. Barriers in accessing health care among trans people is well documented in previous studies [17, 37, 42]. Cruz found that postponement in seeking health care among trans people is mainly caused due to experiences of discrimination [17].…”
Section: Discussionmentioning
confidence: 93%
“…Negative health care experiences were, in addition, found to be associated with poor self-rated health, self-reported disability and lower quality of life. Barriers in accessing health care among trans people is well documented in previous studies [17, 37, 42]. Cruz found that postponement in seeking health care among trans people is mainly caused due to experiences of discrimination [17].…”
Section: Discussionmentioning
confidence: 93%
“…FTM individuals face unique psychological challenges related to gynecologic examinations and Pap testing, and providers lack the knowledge and training to be appropriately equipped to ameliorate these interactions . Additionally, FTM individuals currently face greater rates of health care discrimination, barriers to care, and denial of services (Cruz, 2014;Jaffee et al, 2016;James et al, 2016;Shires & Jaffee, 2015), and health care providers lack knowledge, training, and expertise to provide appropriate care (Unger, 2015).…”
Section: Implications For Nursing Clinical Practicementioning
confidence: 99%
“…Studies rated as poor or satisfactory failed to discuss researchers' reflexivity to a satisfactory standard; however, this was the only criteria where studies rated as satisfactory did not meet the criteria for good quality (Bauer et al, 2009;Lindroth, 2016;Taylor, 2013;Vermeir, Jackson, & Marshall, 2018;von Vogelsang, Milton, Ericsson, & Strömberg, 2016;Westerbotn et al, 2017). Two quantitative studies were appraised as good (Bauer, Zong, Scheim, Hammond, & Thind, 2015;Shires & Jaffee, 2015). Costa et al (2018) was appraised as satisfactory overall.…”
Section: Overview Of Studiesmentioning
confidence: 99%